Geopolitics and Marine Conservation: Synergies and Conflicts - Mackelworth, Peter Charles; Teff Seker, Yael; Vega Fernández, Tomás; Marques, Márcia; Alves, Fátima Lopes; D’Anna, Giovanni; Fa, Darren A.; Goldborough, David; Kyriazi, Zacharoula; Pita, Cristina; Portman, Michelle E.; Rumes, Bob; et al. (Frontiers in Marine Science, 2019)
Transboundary conservation has an important, yet often undervalued, role in the international conservation regime. When applied to the legally ambiguous and interconnected marine environment this is magnified. The lack of clear guidance for transboundary marine conservation from the international conservation community exacerbates this problem, leaving individual initiatives to develop their own governance arrangements. Yet, well-managed transboundary marine protected areas (MPAs) have the potential to contribute significantly to global conservation aims. Conversely, in a period where there is increasing interest in marine resources and space from all sectors, the designation of MPAs can create or amplify a regional conflict. In some instances, states have used MPAs to extend rights over disputed marine resources, restrict the freedom of others and establish sovereignty over maritime space. Six case studies were taken from Europe, North Africa and the Middle East to illustrate how states have interpreted and utilised different legislative mechanisms to either come together or diverge over the governance of marine resources or maritime space. Each of the case studies illustrates how different actors have used the same legislative tools, but with different interpretations and applications, to justify their claims. It is clear that the role of science combined with a deeper engagement with stakeholders can play a critical role in tempering conflict between states. Where states are willing to cooperate, the absence of clear guidelines at the global level means that often ad hoc measures are put into place, with the international frameworks then playing catch up. Balancing different jurisdictional claims with the conservation of the marine environment, whilst considering the increasing special economic interests will become increasingly difficult. Developing a transboundary conservation tool, such as the simple conservation caveats found in the Barcelona Convention and Antarctic Convention, which allow for the establishment of intergovernmental cooperation without prejudicing any outstanding jurisdictional issue, would provide a framework for the development of individual transboundary MPAs.